2014
DOI: 10.2967/jnumed.114.147603
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT Monitoring of β3 Agonist–Stimulated Brown Adipocyte Recruitment in White Adipose Tissue

Abstract: There is rising interest in recruitment of brown adipocytes into white adipose tissue (WAT) as a means to augment energy expenditure for weight reduction. We thus investigated the potential of 18 F-FDG uptake as an imaging biomarker that can monitor the process of WAT browning. Methods: C57BL/6 mice were treated daily with the β3 agonist CL316,243 (5-[(2R)-2-[[(2R)-2-(3-chlorophenyl)-2-hydroxyethyl] amino]propyl]-1,3-benzodioxole-2,2-dicarboxylic acid disodium salt), whereas controls received saline. 18 F-FDG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 28 publications
4
33
1
1
Order By: Relevance
“…There is also evidence that its thermogenic potential is much less than that of iBAT (16,30). Recently, Park et al (35) reported that browning of iWAT following chronic CL treatment (10 days) was associated with an increase in 18 FDG fractional uptake in response to acute CL, a finding that tends to be corroborated by the 18 FDG uptake results of the present study. However, one has to consider that 18 FDG uptake, in contrast to [ 11 C]acetate, does not represent a direct marker of tissue oxidative/thermogenic activity.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…There is also evidence that its thermogenic potential is much less than that of iBAT (16,30). Recently, Park et al (35) reported that browning of iWAT following chronic CL treatment (10 days) was associated with an increase in 18 FDG fractional uptake in response to acute CL, a finding that tends to be corroborated by the 18 FDG uptake results of the present study. However, one has to consider that 18 FDG uptake, in contrast to [ 11 C]acetate, does not represent a direct marker of tissue oxidative/thermogenic activity.…”
Section: Discussionsupporting
confidence: 79%
“…It has been known for years that cold exposure (24 -26, 54) and ␤ 3 -adrenergic agonism (9,17,35,53) both lead to the browning of iWAT. Our results confirm the ability to iWAT to undergo browning after chronic CL and cold and to exhibit increased mtDNA content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated BAT may thus have therapeutic potential to combat both diabetes and obesity with its ability to reduce plasma triglyceride levels [2]. CL316,243, a β3-adrenoceptor selective agonist, has been shown to enhance the uptake of 18 F-FDG in BAT of normal rats [3] and mice [4,5]. More recently another β3-adrenoceptor agonist, mirabegron, has been shown to activate BAT in rats [6] and humans [7].…”
Section: Introductionmentioning
confidence: 99%
“…33,34 After its uptake by the glucose transporter-1 and glucose transporter-4, 29,30 glucose is used for both de novo lipogenesis and ATP generation that supports general adipocyte function. 35 Indeed, BAT activation increases the expression of genes involved in glycolysis and the pentose phosphate pathway; pathways that provide ATP and reducing equivalents for de novo lipogenesis, respectively.…”
Section: Glucose Uptake and Utilization By Batmentioning
confidence: 99%